Generalization of Hermite-Hadamard Integral Inequality via Caputo Fabrizio Fractional Integral Operator (Global Journal of Sciences, 2025)
Certainly, fractional calculus has grabbed the keen interest of numerous investigators in the last couple of decades. Numerous real-world problems and demonstrations have involved the development of the Caputo-Fabrizio fractional operator. Our article’s primary goal is to enhance Hermite-Hadamard (H-H) integral inequality and its generalizations by applying the Caputo-Fabrizio fractional integral operator (CFFIO) and the preinvexity concept. We additionally offer some applications of our key findings to specific methods.
Keywords: Preinvexity; H-H inequality; Caputo-Fabrizio Operator